PENERAPAN METODE JIGSAW DALAM MENINGKATKAN MAHARAH AL-QIRA’AH SISWA KELAS X SMA AL-MAZAAKHIRAH BARAMULI PINRANG: PENELITIAN TINDAKAN KELAS - Asbudi, Ihdina; Nurjannah; Zainal, Abdul Qahar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research discusses the Application of the Jigsaw Method in Improving Maharah Al-Qira'ah of Class X Students of SMA Al-Mazaakhirah Baramuli Pinrang. The purpose of this study is to describe the improvement of Arabic reading skills, as well as to analyze the application of the jigsaw method can improve reading skills and to identify factors that influence the success of the application of the jigsaw method in improving students' reading skills. The type of research used is classroom action research (CAR) which consists of two cycles, each cycle consists of 3 stages, namely planning, action and reflection. The subjects of this study were 19 class X students of SMA Al-Mazaakhirah Baramuli Pinrang. In this study, data collection techniques consisted of observation, tests and documentation. The results of this study indicate that there has been a significant increase in the application of the jigsaw method as evidenced by the results of the observations made. The jigsaw method can improve student learning outcomes, this can be proven in the pre-cycle test, students obtained an average percentage of 64.21 with poor criteria. Cycle I and II saw an increase, namely in cycle I the average percentage was 75.26 and cycle II the average was 83.42. From this analysis it can be said that the application of the jigsaw method is able to improve student learning outcomes, especially improving reading skills.